COMBINED NOISE AND ACOUSTIC FEEDBACK REDUCTION ALGORITHM BASED ON SPECTRAL WEIGHTING RULES FOR SMARTPHONE HEARING AID - M. I. Vashkevich; E. S. Azarov; A. A. Petrovsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The paper presents a combined noise and acoustic feedback reduction algorithm. The algorithm is based on spectral subtraction and is robust to rapid changes in acoustic feedback path which makes it suitable for using in a smartphone-based hearing aid.